A novel single-phase five-level active rectifier for on-board EV battery chargers - Monteiro, Vítor Duarte Fernandes (2017)
This paper presents a novel single-phase active rectifier for applications of on-board EV battery chargers. The proposed active rectifier, with reduced number of semiconductors, is constituted by four MOSFETs and four diodes, and can produce five distinct voltage levels, allowing to reduce the passive filters used to interface with the electrical power grid. An almost sinusoidal grid current with unitary power factor is achieved in the grid side for all the operating power range, contributing to preserve the power quality. The principle of operation, the current control strategy and the modulation technique are presented in detail. Simulation results in different conditions of operation are presented to highlight the feasibility and advantages of the proposed active rectifier.